Laser Photocoagulation : Literature Review - Nailul Authoriyah; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2018)
The increasing role in the use of lasers for medicinal purposes has had an impact on advances in medicine. Laser photocoagulation is a therapy that is widely used for retinal diseases. The invention of lasers revolutionized retinal therapy by facilitating more precise, reliable applications and minimal pain. Based on single wavelength selection, the laser also reduces the amount of damage to adjacent tissue. In the field of medicine other than as curative therapy, laser photocoagulation is also carried out as a preventive measure, preventing the occurrence of more serious complications in these patients. At present, laser photocoagulation as a preventive therapy uses argon laser as its main ingredient. Argon lasers are lasers with green light. The purpose of this burning is to repair diseased or damaged eye tissue so that it can prevent complications that will be caused by persistent diseased or damaged tissue.